Association of HER-2/CEP17 Ratio and HER-2 Copy Number With pCR Rate in HER-2-Positive Breast Cancer After Dual-Target Neoadjuvant Therapy With Trastuzumab and Pertuzumab - Li, Fanfan; Ju, Qian; Gao, Cong; Li, Jingjing; Wang, Xiaolei; Yan, Min; Zhang, Liying; Huang, Meiling; Long, Qihe; Jin, Xiangting; Li, Nanlin (Frontiers in Oncology, 2022)
Objective: To explore the correlation between HER-2 status and pathological complete response (pCR) in HER-2 positive breast cancer after dual anti-HER-2 neoadjuvant therapy with trastuzumab and pertuzumab. Methods: This multicenter, retrospective study enrolled 57 HER-2 positive breast cancer patients admitted to the Second Affiliated Hospital of Anhui Medical University and Xijing Hospital Affiliated to Air Force Military Medical University, between January 1, 2019 and September 30, 2020. HER-2 status, including HER-2/CEP17 ratio and HER-2/cell number ratio, was detected by IHC and FISH. The correlation between HER-2 status/clinicopathological data and pCR was analyzed. The ROC curve was drawn to determine the cutoff value. Results: IHC assessment revealed 40 (70.18%) patients with IHC 3+ and 17 (29.82%) with IHC 2+. 41/57 (71.93%) patients achieved pCR. In multivariate analysis, estrogen receptor (ER) (p=0.022) and PR (p=0.036) proved to be significant predictors of pCR. The pCR rate in ER-negative subgroup and PR-negative patients was 92.86% and 90.63%, respectively. FISH revealed that the ratio of HER-2/chromosome 17 centromere (HER-2/CEP17) (p<0.001) and the ratio of HER-2/cell number (p<0.001) was significantly correlated with the pCR rate. ROC analysis showed that patients with an HER-2/CEP17 ratio ≥4.495 or HER-2/cell number ≥11.650 have a high pCR rate after dual anti-HER-2 neoadjuvant therapy, suggesting its predictive significance. Conclusion: The response to dual-targeted neoadjuvant therapy with trastuzumab and pertuzumab was adequate in hormone receptor-negative, HER-2-positive breast cancer patients. HER-2/CEP17 ratio and HER-2/cell number ratio were crucial for predicting efficacy.